Rivals’ exit and vertical merger evaluation - Donna, J. D.; Pereira, P. (Journal of Competition Law and Economics, 2023)
We discuss a subset of vertical mergers, where the exercise of market power and the efficiencies enabled by a vertical merger reduce rivals' profits, making rivals' exit a potentially serious concern. Rivals' exit can fundamentally alter the welfare analysis of vertical mergers due to the reduction in product variety to consumers and the reduction in the number of competitors that would otherwise exert downward pricing pressure. An exit-inducing vertical merger might reduce welfare even if it is a welfare-enhancing merger absent exit. We present a theoretical framework to analyze vertical mergers that focuses on the possibility and consequences of exit, discuss the antitrust implications for merger evaluation, and provide examples. We argue that the possibility of rivals' exit should be an integral part of the analysis of vertical mergers.